ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN DIET GOUT ARTRITHIS PADA LANSIA - Andriyanto Dai; Sigit Mulyono; Uswatul Khasanah (Journal of Islamic Nursing, 2020)
Attention to non-communicable diseases is increasing because of the increasing frequency of events in the community and requires long-term handling and high costs which are a heavy burden for many people and the Government. Bout Artrithis is the second most non-communicable disease in the elderly based on the 2013 National Health Research. contagious. Lifestyle modification such as low purine diet can reduce uric acid levels and forms of preventive activities, therefore health care prioritizes promotive and preventive health support services and family support so as to increase the knowledge of the elderly and their families in carrying out dietary compliance. The purpose of this study was to determine the analysis of factors related to adherence to the diet of Gout Atrithis in the elderly at the Citizen Health Center in Benteng Palopo. The design of this study was an observational descriptive study using a cross-sectional approach. The results show that the most dominant variable and closely related to diet adherence is knowledge with the relationship of knowledge level with diet adherence showing strength, namely CoBfficients (Exp (B) 5,399). Suggestions are expected to be able to improve health education programs (advertisements in the form of posters, banners and brochures) regarding the importance of diet and understanding about diet for acidic sufferers (Exp (B) 5,399). veins and their families.There needs to be coordination with the health department related to health promotion.Bini health education is carried out in an effort to improve the knowledge of sufferers and families about urinary acidity and matters relating to the management of asamburat illness so that sufferers of uric acid are more adherent to diets that have been recommended by nurses. Keywords: Family Support, Role of Nurses, Knowledge, Diet Compliance, Gout Artrithis.